IDENTIFIKASI PROBLEM REMAJA SISWA KELAS XISMA NEGERI 1 SIMPANG KANANTAHUN PELAJARAN T.P. 2013/2014 - Nurwati '; Elni Yakub Elni Yakub; Sardi Yusuf Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractThe formulation ofthe problem, namely: 1) How wouldthe problem ofadjustment, 2) How canpictureHealthproblems, 3) How wouldthe problem ofEconomicsandgot a job, 4) How wouldwant toplay a roleincommunityproblems, 5) How wouldthe problem ofeducation, 6) Howoverviewthe problem ofspare time, 7) How wouldthe problem ofemploymentandunemployment, 8) Problemteensaremoredominant.The purposeof this research is: 1) Knowingpictureadolescent adjustmentproblemsof class XISMA Negeri1SimpangKanan,2) Knowingpictureadolescenthealthproblemsin class XISMA Negeri1SimpangKanan, 3) Knowingoverviewof economicproblemsandgetthe jobclass teenagersXISMA 1Simpang Kanan, 4) Knowing theproblemdescriptionteenswant toplay a rolein the communityof class XISMA Negeri 1SimpangKanan, 5) Knowing theproblemdescriptionyouthe educationclassXISMA Negeri1SimpangKanan, 6) Knowing theproblemdescriptionspare timeteenclassXISMA 1SimpangKanan, 7) Knowing theproblems ofemploymentandunemploymentpictureteenclassXISMA Negeri 1SimpangKanan, 8) KnowingpictureteenageproblemsmostdominantclassXISMA Negeri1SimpangKanan.Inthis studyusing asample of148students of classXISMA Negeri1SimpangKanan. With22statementquestionnaireformconsists of twocategories, namely witha score of1andnotwith a score of0, then thepictureobtainedadolescentsexperienced by studentsof class XISMA Negeri1Simpang Kananasfollows: Problemadjustment(37.8%), healthproblems(28.2%), economic problemsandget a job(37, 2%), problemswant toplay a rolein the community(47.9%), problemsof education(65.7%), problemspare time(31.1%), problemsemploymentandunemployment(54.4%), andthe mostdominantjuvenileproblemisthe problem ofeducation(65.7%). Keyword: adolleceuces problem